Pengelolaan Website www.bankbjb.co.id Sebagai Media Informasi Digital Oleh Divisi Humas Bank BJB - Alyssa Azka Rinendaputri; Anwar Sani (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The rapid advancement of technology today enables people to meet their information needs through a network called the internet. A website is one of the networks found on the Internet with various functions. The website www.bankbjb.co.id, managed by the Corporate Secretary’s Public Relations Division of Bank BJB, is one of the digital banking information media in Indonesia. The purpose of this research is to understand how the management of the www.bankbjb.co.id website as a digital information medium is carried out by the Public Relations Division of Bank BJB. This research uses a qualitative research method and a descriptive approach that focused on depicting and summarizing various social phenomena that occur. The data collection techniques used include interviews, direct observation of the research object, and documentation. The research results show that the Public Relations Division of Bank BJB, by referring to the concept of the PR management process, has all been implemented.